Marketing Strategies of Aska Soya Milk in Padang - Hakimi, Rini; Hanifah, Mulia; Diana, Yusvi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
Marketing activity is a key factor for the success in business. Success or failure of marketing is highly determined by the applied strategy. This research aimed to identify the factors that affect the volume of sales of ASKA Soy Milk and formulate marketing strategies that can be implemented by ASKA Soy Milk industry to increase the sales volume. This research was conduct with descriptive method. Data collected is the primary and secondary data. Sampling was carried out from retailers by using Cluster Random Sampling. The sample of the consumer is taken by Accidental Sampling and the sampling of the competitors is taken by Purposive. Factors that influence the sales volume of ASKA Soya Milk consist of internal factors such as diverse flavors, incomplete label and the simplicity of a packaging, short product durability, discounts for certain purchases, payment systems consignment, transportation for marketing and promotional. External factors that affect the sales volume of ASKA Soya Milk consist of the existence of local and non-local competitors who produce soy milk with a more attractive appearance and durability, the present of better technologies, and consumer loyalty. The strategy can be implemented by ASKA Soya Milk are: optimizing the use of existing marketing transportation, creating variations product size, complete labeling of products, expand the areas of product marketing, giving more alternate promotion, and providing discounts and rebates to consumers.